The Effect of Coumarin Derivatives(compounds) on the Vibrio cholerae Isolates from Different Clinical Iraqi Sources - Fatima .R.Abdul; Nehad .A.Taher; Ashraf S.Hassan; Enaam H. Batah (Iraqi Journal of Pharmaceutical Sciences, 2017)
From a large number of bacterial samples collected from different hospital in Iraq in central  health laboratory ,only ten isolates were identified primary as Vibrio. A number of  morphology and biochemical test were carried out to complete this identification that showed all bacterial isolates were related to Vibrio cholerae .In this study  all Vibrio isolates were investigated for Bio typing and the result showed that all (10) isolate were related to (Eltor biotypes) .Also, the susceptibility test towards eight antibiotics were carried  out .